Scalable and flexible location-based services for ubiquitous information access - José, Rui (1999)
In mobile distributed environments applications often need to dynamically obtain information that is relevant to their current location. The current design of the Internet does not provide any conceptual models for addressing this issue. As a result, developing a system that requires this functionality becomes a challenging and costly task, leading to individual solutions that only address the requirements of specific application scenarios. In this paper we propose a more generic approach, based on a scalable and exible concept of location-based services, and an architectural framework to support its application in the Internet environment. We describe a case study in which this architectural framework is used for developing a location-sensitive tourist guide. The realisation of this case study demonstrates the applicability of the framework, as well as the overall concept of location-based services, and highlights some of the issues involved.